Large-scale, high-resolution electrophysiological imaging of field potentials in brain slices with microelectronic multielectrode arrays - Ferrea, Enrico; Maccione, Alessandro; Medrihan, Lucian; Nieus, Thierry; Ghezzi, Diego; Baldelli, Pietro; Benfenati, Fabio; Berdondini, Luca (Frontiers in Neural Circuits, 2012)
Multielectrode arrays are extensively used for electrophysiological studies on brain slices, but the spatial resolution and field of recording of conventional arrays are limited by the low number of electrodes available. Here, we present a large-scale array recording simultaneously from 4096 electrodes used to study propagating spontaneous and evoked network activity in acute murine cortico-hippocampal brain slices at unprecedented spatial and temporal resolution. We demonstrate that multiple chemically-induced epileptiform episodes in the mouse cortex and hippocampus can be classified according to their spatio-temporal dynamics. Additionally, the large-scale and high density features of our recording system enable the topological localization and quantification of the effects of antiepileptic drugs in local neuronal microcircuits, based on the distinct field potential propagation patterns. This novel high resolution approach paves the way to detailed electrophysiological studies in brain circuits spanning spatial scales from single neurons up to the entire slice network.